Green human resource management: A bibliometric analysis - Jéssica Fachada; Teresa Rebelo; Paulo Lourenço; Isabel Dórdio Dimas; Helena Martins (Administrative Sciences, 2022)
Despite the growing attention which green human resource management (GHRM) has been gaining, the field is still remarkably young, and conceptual clarity is yet to be attained. A bibliometric review of GHRM from 2010 to 2020 was conducted on the Web of Science and analyzed using the VOSviewer software package, version 1.6.16 developed by Van Eck and Waltman (Leiden, The Netherlands). The results show the exponential growth of this topic, although there seems to be no consensus regarding its definition, conceptualization and measurement. Concerning its conceptual development, GHRM seems to currently fit the second stage of development (evaluation and augmentation) of Reichers and Schneider's three-stage model of the evolution of constructs. Future research seems to point in the direction of establishing the barriers separating GHRM from other human resource management topics, defining green practices and determining the antecedents and consequences of GHRM.
Keywords: 350; bibliometric analysis; corporate social responsibility; green human resource management; green practices; sustainability